A multilevel fault-tolerant power converter for a switched reluctance machine drive - Fernao Pires, Vitor (2020)
Reliability in the electrical drives is becoming an important issue in many applications. In this context, the reliability associated to the switched reluctance machine (SRM) is also an important area of research. One of the major problems, that strongly affect its operation, are drive power semiconductors faults. Typical power converter topologies used in SRM drives cannot handle faults in their power semiconductors. So, this paper presents a power converter topology that provides fault-tolerant capabilities to the drive under a switch fault. This power converter will be used considering that a change in the direction of the current that flows in the SRM windings does not affect the behavior of the machine. Besides that, the proposed power converter will allow to generate multilevel phase voltages in order to apply different voltage levels as function of the SRM speed. A laboratory power converter was developed to test the SRM drive in normal and faulty conditions. From the obtained results it was possible to verify the fault-tolerant capability of the drive under switch faults in different devices and failure modes. It was also possible to confirm the multilevel operation of the drive.